The competence of EU institutions to adopt directives regulating substantive criminal law - Gruew, Georgi (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper focuses on the competence of the European Parliament and the EU Council to adopt directives in the area of substantive criminal law provided in Articles 83 and 84 of the TFEU, which confirm the earlier ECJ rulings on the subject. The competence granted to those institutions also ensure greater effectives of the adopted directives in combating serious crimes within the European Union. The creation of certain ‘emergency brakes’ and application of the principle of proportionality taking into account the fundamental principles of criminal law systems of individual Member States, has enabled the EU institutions to establish common definitions of most serious crimes.